THE REFLECTION OF ERNEST HEMINGWAY’S LIFE EXPERIENCES IN THE MAIN CHARACTERS OF CAT IN THE RAIN - YULYANANDA, BRAMANTYA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Ernest Hemingway, short story, character, mimetic.A short story is a medium to reflect past personal experiences of an author. So as Ernest Hemingway who created every character is a reflection of his past personal experiences.The research of Hemingway’s short story Cat in the Rain used biographical approach and mimetic theory to identify imitation and reality from every behaviour that was shown by the  main characters. Through the text and author’s biography, the relation between the main characters in his short story Cat in the Rain with his personal life can be seen and identified.The result of this research shows Ernest Hemingway’s expertise in adding part of his personal experience into the character in his works. In Cat in the Rain, he reveals the man who has some mode of thought and the woman has some emotional state. The man is a masculine person, controlling towards the behaviour of his wife, and having an intelectual personality the same as Hemingway’s environment in the past. Whereas the wife is a person who is mercifull with the living things, needs attention and protection, a lonely person, lack of confidence with her appearance, bounded by her husband, and feels hopeless with her life the same as Hemingway’s feeling in the past.